2016
DOI: 10.2334/josnusd.15-0658
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of the debris apically extruded during three different retreatment procedures

Abstract: Abstract:We evaluated the cytotoxic effects of the debris apically extruded during root canal retreatment on primary human osteoblast (HOb) cells in vitro. TNF-α and IL-1β levels were also measured. We examined three different techniques: conventional hand-files, and Mtwo and Reciproc retreatments. Filled mandibular incisors were prepared for a cytotoxicity assay in an experimental root model. The material was divided into three groups according to the technique used. Ten teeth were used as control. HOb cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…8,15,21 Regarding movement, recent studies have shown that rotatory or reciprocating movement does not have significant differences in relation to extrusion of debris and root filling removal during root canal retreatment. 30,31 In our research, although the smaller extrusion occurred in the retreatment group with Mtwo and Reciproc instruments, this difference was not statistically significant. This result may have been due to the association of instruments with different kinematics, where continuous rotation was used to remove the root filling material and reciprocating movement to enlarge apical third, causing less extrusion than the techniques that used a single type of movement.…”
Section: Discussioncontrasting
confidence: 58%
“…8,15,21 Regarding movement, recent studies have shown that rotatory or reciprocating movement does not have significant differences in relation to extrusion of debris and root filling removal during root canal retreatment. 30,31 In our research, although the smaller extrusion occurred in the retreatment group with Mtwo and Reciproc instruments, this difference was not statistically significant. This result may have been due to the association of instruments with different kinematics, where continuous rotation was used to remove the root filling material and reciprocating movement to enlarge apical third, causing less extrusion than the techniques that used a single type of movement.…”
Section: Discussioncontrasting
confidence: 58%
“…12 A recent study showed that reciprocating technique was effective in endodontic retreatment, requiring less time than rotary and hand files. 19,27,3 The present study was designed to evaluate the ability of Reciproc System to remove root canal filling material from the canal with or without solvent. Despite the undesirable properties of chloroform, such as the local toxicity in contact with periradicular tissues, hepatotoxicity and nephrotoxicity, 31,32 it is the most efficient gutta-percha solvent and one of the most used in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Even though there is accumulating evidence of safety and shaping effectiveness of the reciprocating motion, [13][14][15][16] knowledge of the potential benefits of using this system in retreatment cases is still lacking. [17][18][19] Nevertheless, there is no agreement about which methods should be used for root canal filling removal using reciprocating motion.…”
Section: Introductionmentioning
confidence: 99%
“…Although extruded root filling material may provoke a foreign body induced inflammatory response, which may cause patients to experience pain, the bacterial content of the extruded material may be more responsible for any postoperative pain; therefore, in order to draw any clinical conclusions, the bacterial content of the extruded material may be more relevant. Silva et al (2016) investigated the inflammatory effect of extruded debris by measuring the cytotoxicity and the cytokine levels produced. However, as the tooth samples were disinfected with 0.5% chloramine T before any procedures were carried out and sterilized with ethylene oxide gas after the canals were accessed, the measured inflammatory effect may not be due to any bacterial cause but rather as a result of a foreign body reaction.…”
Section: Apical Extrusion Of Root Filling Materialsmentioning
confidence: 99%
“…Other methods of assessing apical extrusion of root filling material include direct visual inspection by noting its presence or absence (Rehman et al, 2013). The quantity of debris is then further assessed according to a qualitative scoring system (Silva et al, 2015; Yadav et al, 2013), using radiographic imaging techniques (Canali et al, 2019; Chandrasekar et al, 2014; Dhaimy et al, 2021) or by measuring the cytotoxicity and cytokine production levels caused by the extruded material (Silva et al, 2016). Invariably, the apically extruded debris is a mixture of dentine chips and root filling material.…”
Section: Other Variablesmentioning
confidence: 99%